2021
DOI: 10.1038/s41598-021-91237-9
|View full text |Cite
|
Sign up to set email alerts
|

Irrelevant task suppresses the N170 of automatic attention allocation to fearful faces

Abstract: Recent researches have provided evidence that stimulus-driven attentional bias for threats can be modulated by top-down goals. However, it is highlight essential to indicate whether and to what extent the top-down goals can affect the early stage of attention processing and its early neural mechanism. In this study, we collected electroencephalographic data from 28 healthy volunteers with a modified spatial cueing task. The results revealed that in the irrelevant task, there was no significant difference betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…The former finding is in line with several recent behavioral (Koster et al, 2007;Hedger, et al, 2015a; and electrophysiological studies (Pegna et al, 2008;Del Zotto and Pegna, 2015;Grassini et al, 2016;Schlossmacher et al, 2017;Qiu et al, 2022), which also found that threat signals do not engage attention pre-consciously. The finding that attentional bias is not entirely automatic supports the view that context-related factors shape the scope of attentional prioritization of threats, and it provides further evidence that top-down processes can influence various stages of fear reaction (Pessoa et al, 2002;Holmes, Vuilleumier, Eimer, 2003;Pessoa, 2005;Silvert et al, 2007;Eimer and Kiss, 2008;Brosch and Wieser, 2011;Dou et al, 2021;Tipura and Pegna, 2022). Collectively, this body of work supports the "many roads" hypothesis, which assumes that reaction to threats is not based on the purely sensory assessment of the stimulus and is not encapsulated; instead, it involves a complex interplay between subcortical and cortical areas and is likely based on fine-grained stimulus evaluation involving conscious perception and top-down attention (Pessoa and Adolphs, 2010).…”
Section: Lack Of Unconscious Attentional Prioritization -Theoretical ...supporting
confidence: 56%
“…The former finding is in line with several recent behavioral (Koster et al, 2007;Hedger, et al, 2015a; and electrophysiological studies (Pegna et al, 2008;Del Zotto and Pegna, 2015;Grassini et al, 2016;Schlossmacher et al, 2017;Qiu et al, 2022), which also found that threat signals do not engage attention pre-consciously. The finding that attentional bias is not entirely automatic supports the view that context-related factors shape the scope of attentional prioritization of threats, and it provides further evidence that top-down processes can influence various stages of fear reaction (Pessoa et al, 2002;Holmes, Vuilleumier, Eimer, 2003;Pessoa, 2005;Silvert et al, 2007;Eimer and Kiss, 2008;Brosch and Wieser, 2011;Dou et al, 2021;Tipura and Pegna, 2022). Collectively, this body of work supports the "many roads" hypothesis, which assumes that reaction to threats is not based on the purely sensory assessment of the stimulus and is not encapsulated; instead, it involves a complex interplay between subcortical and cortical areas and is likely based on fine-grained stimulus evaluation involving conscious perception and top-down attention (Pessoa and Adolphs, 2010).…”
Section: Lack Of Unconscious Attentional Prioritization -Theoretical ...supporting
confidence: 56%
“…Findings of greater amplitudes for angry and fearful, less so for happy faces, in comparison with neutral faces additionally suggest that not only processing of configural information but also of emotional cues occurs during this time window (Hinojosa et al, 2015). Although it has been suggested that the N170 sensitivity to emotional expression might depend on attention to emotional features (Dou et al, 2021; Kolassa et al, 2007; Kolassa & Miltner, 2006; Wronka & Walentowska, 2011), the emotion modulation can also be seen in tasks involving automatic processing (Hinojosa et al, 2015; Schindler & Bublatzky, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For N170 and EPN, we aimed to find larger amplitudes for emotional than neutral expressions (Hinojosa et al, 2015; Rellecke et al, 2012; Schindler & Bublatzky, 2020; Williams et al, 2006). What is more, there have been findings of an increased face‐N170 arousal effect when attention was focused on emotion in general compared with attention to non‐emotional features (Dou et al, 2021; Kolassa et al, 2007; Wronka & Walentowska, 2011). Following these earlier studies and the reported attention‐sensitivity of N170, we expected that a task involving selective attention to emotional expressions would similarly elicit more pronounced N170 arousal effects in target faces than in nontarget faces.…”
Section: Introductionmentioning
confidence: 99%